ChemInform Abstract: Suzuki Coupling Reaction in the Presence of Polymer Immobilized Palladium Nanoparticles: A Heterogeneous Catalytic Pathway. Issue 45 (November 2015) - Taher, Abu; Nandi, Debkumar; Choudhary, Meenakshi; Mallick, Kaushik
Abstract A Pd—poly(1, 2‐diaminobenzene) composite material with palladium nanoparticles with an average size of 3 nm are synthesized from 1, 2‐diaminobenzene (DAB) and K2PdCl4 and successfully used as a catalyst for Suzuki coupling reactions in the absence of any phosphine ligand.